Concealment in a dynamic world: dappled light and caustics mask movement. (September 2018) - Matchette, Samuel R.; Cuthill, Innes C.; Scott-Samuel, Nicholas E.
Abstract : The environment plays a significant role in shaping the visibility of signals both to and from an organism. For example, against a static background movement is highly conspicuous, which favours staying still to optimize camouflage. However, backgrounds can also be highly dynamic, such as areas with wind-blown foliage or frequent changes in illumination. We propose that these dynamic features act as visual noise which could serve to mask otherwise conspicuous movement. Two forms of illumination change were simulated, water caustics and dappled light, to represent dynamic aquatic and terrestrial environments, respectively. When asked to capture moving prey items within the simulated scenes, human participants were significantly slower and more error prone when viewing scenes with dynamic illumination. This effect was near identical for both the aquatic and terrestrial environments. In the latter, prey item movement was also found to be masked most often when the pathway taken involved movement across the dynamic dappled areas of the scene. This could allow particularly moving prey to reduce their signal-to-noise ratio by behaviourally favouring the relative safety of environments containing dynamic features. Highlights: Environments contain dynamic features, which introduce visual noise. Visual noise reduces the signal-to-noise ratio and can mask conspicuous signals. Movement of prey items is masked by dynamic features in simulated scenes. Masking is consistent for prey movement in terrestrial and aquatic simulations.